Against Disease, Suffering, and Other Plagues: the Magic-healing Role of Thunderstones in the Middle Ages and Modern Times - Tomasz Kurasiński (Fasciculi Archaeologiae Historicae)
Prehistoric stone objects (most often Neolithic) referred to as ‘thunderstones’ in the Middle Ages and modern times have been assigned various meanings – primarily they are supposed to have been used to protect against lightning, fire, and other natural disasters. They have also found application in folk medicine and healing magic (protection against the harmful effects of disease and loss of fertility, and neutralisation of misfortune when it has already occurred). Trust in their magical (apotropaic) properties was probably associated with the belief that these objects originated from outside the sphere of the ‘tame’ world. Folklore and ethnographic data, as well as traces of use preserved in archaeological monuments, support a long tradition of therapeutic use of thunderstones, which is a pan-European phenomenon.